1963
DOI: 10.1037/h0046337
|View full text |Cite
|
Sign up to set email alerts
|

A sex difference in the age of onset of the parent-child resemblance in intelligence.

Abstract: In a representative urban sample of 248 children, years of schooling of both parents showed an increasing relationship to their son's and daughter's IQs between 21 mo. and 15 yr. The parent-child correlation was observable and became statistically significant for girls by 3 yr. but not until 5 yr. for boys. Earlier parent-daughter resemblance was also noted when ratings of mother's intelligence and social status were correlated with the children's scores. Siblings' IQs yielded comparable sex differences in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
17
0

Year Published

1965
1965
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 14 publications
6
17
0
Order By: Relevance
“…These findings are consistent with those of Kagan and Moss (1959) and Honzik (1963), who reported an association between the child's I.Q,-and status characteristics of the parents, in their cases parental I.Q. and education, at an earlier age among girls than boys.…”
Section: Sex and Social Class Differencessupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with those of Kagan and Moss (1959) and Honzik (1963), who reported an association between the child's I.Q,-and status characteristics of the parents, in their cases parental I.Q. and education, at an earlier age among girls than boys.…”
Section: Sex and Social Class Differencessupporting
confidence: 93%
“…Scores at both ages were significantly correlated with mother's education, but only at 5 yr with that of the father. The generally higher correlations at 5 yr, with each of the parental status variables, are consistent with the findings of Bayley 1954) and Honzik (1957Honzik ( , 1963). Because of its high level of discrimination, father's occupation was used as the criterion of social class in further comparisons.…”
Section: Sex and Social Class Differencessupporting
confidence: 88%
“…The results from these several studies are quite consistent in suggesting that parental education begins to relate to the child's IQ performance between 11/ and 3/2 years for girls but not until 2/2 to 6 years for boys (Bayley & Jones 1937;Goodenough 1927;Hindley 1965;Honzik 1963;Kagan & Moss 1959;Moore 1968;Rees & Palmer 1970). Although the precise age at which the correlational relationship is first statistically significant varies among studies (i.e., presumably as a function of the nature of the sample, sample size, specific test instruments, testing regimen, etc.…”
Section: Parental Educationsupporting
confidence: 54%
“…Some investigators have found higher relationships with mother's education than with father's, especially during the 11/2-3-year period (Bayley & Jones 1937;Kagan & Moss 1959). Others do not find this parental sex difference (Goodenough 1927;Honzik 1963;Werner, Honzik, & Smith 1968), although the parental correlations may be higher for boys than girls (Werner et al 1968). …”
Section: Parental Educationmentioning
confidence: 88%
“…First, there is a great deal of evidence, in psychology, of developmental variations in the relationships between cognitive, demographic and background variables. For example, the correlation between parents' education or socioeconomic status and intelligence test scores of their offspring is negative or close to zero during early childhood but increases to .40-.60 in the following years (e. g., Bayley & Jones, 1937;Bayley, 1954Bayley, , 1970Honzik, 1957Honzik, , 1963Honzik, , 1967. Also, the IQ variance explained by genotype increases with age whereas the effect of shared environmental influences tends to diminish between childhood and adolescence (Plomin, 2003;Plomin, DeFries, McClearn, & McGuffin, 2001;Plomin & Petrill, 1997;Plomin & Spinath, 2004).…”
mentioning
confidence: 97%